The Impact of the Number of Injections per Visit on the Likelihood of Human Papillomavirus Immunization - Steve G. Robison, MPH (Elsevier, 2020)
Objective: To test whether adolescents, who are injection limited, that is, receiving only a limited number of immunization injections per visit, are less likely to complete the human papillomavirus (HPV) immunization series. Study design: For Oregon adolescents age 13-17 years, HPV series completion rates were assessed based on never receiving >1 injection per visit from age ≥9 years. Among a study subset born and resident in Oregon through adolescence, HPV series rates were assessed based on never receiving >1 or 2 injections per visit from age ≥4 years. Cox proportional hazards regression was used to assess delays owing to limiting injections, controlling for sex and rural location. Results: Among 241 453 study adolescents, 16.3% had only single-injection visits from age ≥9 years. Their HPV completion rate was 7.7% as compared with 61.7% for those with no limitations of number of injections. Among study adolescents born in Oregon, 10.2% never received >1 or 2 injections per visit from age ≥4 and were less than half as likely to complete the HPV series (28.4% vs 59.1%). Conclusions: Limiting the number of injections per visit is associated with decreased completion of HPV immunization. As larger cohorts of young children with early injection-limiting characteristics age into adolescence, progress on HPV immunization rates may be challenged.